2018
DOI: 10.1080/13670050.2018.1472206
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing CLIL teaching: new insights from a lower secondary classroom

Abstract: As a bilingual teaching method, Content and Language Integrated Learning (CLIL) is growing in popularity in Europe and research has primarily focused on (language) learning outcomes.Few studies have identified what characterizes teaching in the CLIL classroom in terms of content and language integration. Studying how CLIL is practiced is vital to understanding how it works and how students can benefit from it. In this study, we filmed and observed CLIL lessons in science and mathematics in a 9 th grade, Norweg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 64 publications
1
36
1
1
Order By: Relevance
“…According to McNeil (2011), key scaffolding strategies include revoicing (repeating the student's answer in academic language), repetition (echoing a student's answer in class), and elaboration (prompting the student to justify or lengthen their answer) (398). Mahan, Brevik and Ødegaard (2018) provide evidence of these three scaffolding strategies in CLIL teaching, but they found more strategies in mathematics than in science. The science discourse included more patterns of Initiation-Response-Evaluation (IRE).…”
Section: Task-solving Strategies In Sll Scaffoldingmentioning
confidence: 79%
See 4 more Smart Citations
“…According to McNeil (2011), key scaffolding strategies include revoicing (repeating the student's answer in academic language), repetition (echoing a student's answer in class), and elaboration (prompting the student to justify or lengthen their answer) (398). Mahan, Brevik and Ødegaard (2018) provide evidence of these three scaffolding strategies in CLIL teaching, but they found more strategies in mathematics than in science. The science discourse included more patterns of Initiation-Response-Evaluation (IRE).…”
Section: Task-solving Strategies In Sll Scaffoldingmentioning
confidence: 79%
“…Gallagher and Colohan (2017) argue that L1 can be a powerful scaffolding strategy in CLIL contexts (in which students and teachers have a common L1 and cultural background). Mahan, Brevik and Ødegaard (2018) and Dalton-Puffer (2007) have found that CLIL teachers frequently use L1 as a resource for helping students comprehend, drawing connections between concepts in L1 and L2.…”
Section: Comprehension Strategies In Sll Scaffoldingmentioning
confidence: 99%
See 3 more Smart Citations